Fall of the World Trade Centre - Lynch, John; Fortune, Jack; Kennedy, Garfield
Explores the minute by minute story of how the two towers of the World Trade Centre collapsed and gives the first scientific explanation of why New York's tallest buildings failed so catastrophically. The towers fell in different ways and for differenct reasons. There are implications for anyone who designs, builds or even works in a tall building. Can anything make skyscrapers safe from attack in the future?